Rheological, thermal and mechanical characterization of PBAT/PCL/Stearates blends - Silva, Jessé de Melo (2022)
The slow degradation and the high environmental impact caused by inappropriate disposal of polymer products are the main factors prompting scientists to either substitute conventional polymers by biodegradable ones or to enhance biodegradation of short-lived polymer products, particularly those used in packaging. Polymer blends of conventional and biodegradable polymers is one of the alternative solutions found to improve mechanical properties and accelerate polymer degradation after disposal. This work investigates the effect of incorporating different metallic stearates (Zn and Mg) on the rheological, thermal and mechanical characteristics of 75PBAT/25PCL blends processed in an internal laboratory mixer. The results of torque rheometry suggest degradation during processing potentialized with the stearates incorporation, while that of DSC indicated that the crystallinity of the blends increased with the incorporation of additives. TG data showed a reduction in the thermal stability of the systems containing stearates. Incorporation of stearates resulted in strongly thermally degraded systems. Adding up to 0.25% of magnesium stearate to the blend 75PBAT/25PCL leads to a material that combines maintenance or improvement of properties combined with higher decomposition.